Selvskade hos psykiatriske patienter - Møhl, Bo; Rubæk, Lotte (Psyke & Logos, 2016)
58 self-harming patients in psychiatric treatment have been investigated by a self-report questionnaire with focus on self-harm methods and frequency, circumstances of the selfharm episode, motivation for and effect of self-harm and suicidal attempts. The participants in the study have on average used 8 different self-harm methods. 93% have cut themselves, 57.7% have done so more than 50 times. 93% were usually alone when injuring themselves and 41.8% felt no pain associated with self-harm. Affect regulation is the most frequent motif, and the majority reported a significant reduction in negative emotions such as anger, fear and guilt after the self-harm episode. 68.4% had attempted suicide, 41.5% more than 5 times. Participants with a history of attempted suicide have more frequently been abused in childhood. The study documents that psychiatric patients have severe forms of self-injury, and finally clinical implications are discussed.